One Health: A new definition for a sustainable and healthy future - Adisasmito, Wiku B.; Almuhairi, Salama; Behravesh, Casey Barton; Bilivogui, Pépé; Bukachi, Salome A.; Casas, Natalia; Cediel Becerra, Natalia; Charron, Dominique F.; Chaudhary, Abhishek; Ciacci Zanella, Janice R.; Cunningham, Andrew A.; Dar, Osman; et al. (PLoS pathogens, 2022)
Following a proposal made by the French and German Ministers for Foreign Affairs at the November 2020 Paris Peace Forum, 4 global partners, the Food and Agriculture Organization (FAO), the World Organization for Animal Health (OIE), the United Nations Environment Programme (UNEP), and the World Health Organization (WHO), in May 2021 established the interdisciplinary One Health High-Level Expert Panel (OHHLEP) (https://www.who.int/groups/one-health-high-level-expert-panel) to enhance their cross-sectoral collaboration. There is no shortage of “One Health” definitions in the published literature and among institutions and organizations. [...]an immediate priority for OHHLEP was to develop consensus around a working definition as a solid basis to support a common understanding among the panel members and the partner organizations. Key underlying principles including 1. equity between sectors and disciplines; 2. sociopolitical and multicultural parity (the doctrine that all people are equal and deserve equal rights and opportunities) and inclusion and engagement of communities and marginalized voices; 3. socioecological equilibrium that seeks a harmonious balance between human–animal–environment interaction and acknowledging the importance of biodiversity, access to sufficient natural space and resources, and the intrinsic value of all living things within the ecosystem; 4. stewardship and the responsibility of humans to change behavior and adopt sustainable solutions that recognize the importance of animal welfare and the integrity of the whole ecosystem, thus securing the well-being of current and future generations; and 5. transdisciplinarity and multisectoral collaboration, which includes all relevant disciplines, both modern and traditional forms of knowledge and a broad representative array of perspectives. PLoS Pathog 18(6): e1010537. https://doi.org/10.1371/journal.ppat.1010537 About the Authors: One Health High-Level Expert Panel (OHHLEP) Wiku B. Adisasmito Affiliation: Universitas Indonesia, Depok, West Java, Indonesia Salama Almuhairi Affiliation: National Emergency Crisis and Disasters Management Authority, Abu Dhabi, United Arab Emirates Casey Barton Behravesh Affiliation: Centers for Disease Control and Prevention, Atlanta, Georgia, United States of America Pépé Bilivogui Affiliation: World Health Organization, Guinea Country Office, Conakry, Guinea Salome A. Bukachi Affiliation: Institute of Anthropology, Gender and African Studies, University of Nairobi, Nairobi, Kenya Natalia Casas Affiliation: National Ministry of Health, Autonomous City of Buenos Aires, Argentina Natalia Cediel Becerra Affiliation: School of Agricultural Sciences, Universidad de La Salle, Bogotá, Colombia Dominique F. Charron Affiliation: International Development Research Centre, Ottawa, Canada Abhishek Chaudhary Affiliation: Indian Institute of Technology (IIT), Kanpur, India Janice R. Ciacci Zanella Affiliation: Brazilian Agricultural Research Corporation (Embrapa), Embrapa Swine and Poultry, Concórdia, Santa Catarina, Brazil Andrew A. Cunningham Affiliation: Institute of Zoology, Zoological Society of London, London, United Kingdom Osman Dar Affiliations Global Operations Division, United Kingdom Health Security Agency, London, United Kingdom, Global Health Programme, Chatham House, Royal Institute of International Affairs, London, United Kingdom Nitish Debnath Affiliation: Fleming Fund Country Grant to Bangladesh, DAI Global, Dhaka, Bangladesh Baptiste Dungu Affiliations Afrivet B M, Pretoria, South Africa, Faculty of Veterinary Science, University of Kinshasa, Kinshasa, Democratic Republic Congo Elmoubasher Farag Affiliation: Ministry of Public Health, Health Protection & Communicable Diseases Division, Doha, Qatar George F. Gao Affiliation: Chinese Center for Disease Control and Prevention, Beijing, People’s Republic of China David T. S. Hayman Affiliation: Molecular Epidemiology and Public Health Laboratory, Massey University, Palmerston North, New Zealand Margaret Khaitsa Affiliation: Mississippi State University, Starkville, Mississippi,